Hydrogen Absorption in Palladium‐Based Nanocrystals for Electrocatalysis Investigation - Ying Chen; Yucheng Hou; Gennady Govor; Olga Demidenko; Yujing Li (ChemElectroChem, 2024)
Abstract Hydrogen absorption in transition metals has received enormous attention for applications such as the hydrogen storage, sensing and corrosion. In particular, the Pd‐H system is a simple and classical metal hydride system that serves as a platform for a deeper understanding of hydrogen behavior. In the past few years, Pd‐H has been reported as electrocatalyst in multiple reactions, whereas the impact of hydrogen absorption/desorption in electrocatalytic applications remains unclear. Therefore, in this concept, factors influencing the hydrogen adsorption/desorption of palladium in the gas phase, such as facet engineering, ligand effects, and alloying effects, are summarized. Subsequently, in the context of electrocatalysis, factors affecting electrochemical hydrogen adsorption/desorption are outlined. Particularly, prospects for the further investigation of electrochemical hydrogen adsorption/desorption in catalysis are discussed.